2004
DOI: 10.1081/pb-120027117
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Catalyzed Synthesis of Some Vinyl Drug Esters in Organic Medium

Abstract: A series of vinyl drug esters was synthesized using acyclovir and chloramphenicol with different carbon chain length acyl donors by alkaline protease from Bacillus subtilis and Lipozyme respectively, in non-aqueous medium. The corresponding vinyl drug derivatives were confirmed by nuclear magnetic resonance and infrared spectrometry. The influences of different organic solvents, reaction time, temperature, and content of water on synthesis of vinyl chloramphenicol esters were studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The conversion was calculated by high pressure liquid chromatography (Waters 2690 Separations Module; Waters 2487 UV vis Dual Absorbance Detector; readings were made at 273 nm) using a silica gel column (Agilent C18, 4.6 × 150 mm) and eluted with 0.01 M phosphoric acid/acetonitrile (85:15, v/v%) with a flow rate of 0.6 mL/min [8]. The products were identified by FTIR, 1 H-NMR (400 MHz, CDCl 3 ), and 13 C-NMR (101 MHz, CDCl 3 ) on a JEOL RESONANCE ECZ 400S spectrometer.…”
Section: Chloramphenicol Palmitate Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The conversion was calculated by high pressure liquid chromatography (Waters 2690 Separations Module; Waters 2487 UV vis Dual Absorbance Detector; readings were made at 273 nm) using a silica gel column (Agilent C18, 4.6 × 150 mm) and eluted with 0.01 M phosphoric acid/acetonitrile (85:15, v/v%) with a flow rate of 0.6 mL/min [8]. The products were identified by FTIR, 1 H-NMR (400 MHz, CDCl 3 ), and 13 C-NMR (101 MHz, CDCl 3 ) on a JEOL RESONANCE ECZ 400S spectrometer.…”
Section: Chloramphenicol Palmitate Characterizationmentioning
confidence: 99%
“…Ottolina et al reported the regioselective synthesis of several derivatives using Chromobacterium viscosum lipase and lipase G in acetone, thus obtaining excellent yields (98%) after 24 h at 45 • C [4]. Later, Lv et al reported the synthesis of chloramphenicol vinyl esters using Lipozyme from Bacillus subtilis, thereby demonstrating the versatility of hydrolases [8]. Among chloramphenicol derivatives, chloramphenicol palmitate has been studied only in a few works.…”
Section: Introductionmentioning
confidence: 99%
“…8 Later, Lin and co-workers demonstrated the versatility of hydrolases such as Lipozyme or A R T I C L E I N F O A B S T R A C T the protease from Bactillus subtilis in the synthesis of chloramphenicol vinyl esters. 9 Herein we develop the synthesis of a wide set of chloramphenicol esters by using complementary synthetic approaches such as acylation and hydrolysis processes. We have especially focused on the optimisation of the reaction conditions including the scaling-up and the enzyme recycling outcome.…”
Section: Introductionmentioning
confidence: 99%
“…This effect can be explained because diacylated compound b and c could not correctly fit in the active site of Lip BA . The above achievements suggest Lip BA lipase is an ideal catalyst for the regioselective acylation of chloramphenicol, showing an excellent selectivity for the acylation of the primary alcohol [ 8 , 17 ]. The molar ratio of chloramphenicol to vinyl propionate had a significant effect on the conversion of the product.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in our previous report, this enzyme was used in biocatalysis and cinnamyl esters were synthesized using lipase (Lip BA ) through the transesterification route in a non-aqueous system with vinyl propionate as the best acyl donor [ 16 ]. In this study, we have developed a chloramphenicol ester synthesis by using different carbon chain length acyl donors [ 17 ]. Among the acyl donors with different carbon chain lengths, vinyl propionate was chosen to act as the best acyl donor.…”
Section: Introductionmentioning
confidence: 99%